Evaluation of Lung Contusion, Associated Injuries, and Outcome in a Major Trauma Center in Shiraz, Southern Iran - Parviz Mardani; Mohammad Moayedi Rad; Shahram Paydar; Armin Amirian; Reza Shahriarirad; Amirhossein Erfani; Keivan Ranjbar (Emergency Medicine International)
Objective. Blunt chest trauma as one of the most common injuries in trauma cases can cause significant morbidity and mortality. The purpose of this study was to determine the clinical course of traumatic injuries with an initial diagnosis of a pulmonary contusion in patients. Method. In this retrospective study, we evaluated the demographic and clinical features of patients who were referred to a major trauma center in southern Iran. In our study, patients were enrolled with the diagnosis of pulmonary contusion. All included patients were above 16 years of age, with an initial CT scan in favor of pulmonary contusion, while patients not being hospitalized for more than 48 hours were excluded from the study. Results. Among the 434 patients included in our study, 366 (84%) were male and the mean age was 41.17 (SD = 17.89). Among them, the majority (80.4%) had right side lung contusion and 47 patients (10.8%) had right rib fracture. The most common injuries were head and neck injury (56.9%) and limbs (30%). In 25% of cases, pulmonary contusion was associated with pneumothorax and 15.8% with hemothorax. Also, 49.6% of patients were transferred to the ICU. The mortality rate in our study was 15.2% (n = 66). Conclusion. Although recent advances in pulmonary care and ventilator management have been achieved, there is still considerable morbidity and mortality associated with this condition. Therefore, there is a need to provide a national guideline based on native patient information for better management.